Enkulturasi Budaya: Pola Pewarisan Tradisi Menenun pada Generasi Muda di Desa Pringgasela Lombok Timur - Sukria Novianti; Muhammad Ruslan; Muhammad Khaerul Rizal; Muhammad Taupik Alfarizi; Jepri Utomo; Milla Noviana (Universitas Palangka Raya, 2026)
The low interest of the younger generation in traditional crafts threatens the preservation of Nusantara textiles. A study entitled